Second-Personal Desire. Issue 4 (21st March 2017) - LEITE, ADAM
ABSTRACT: This paper concerns desires with a distinctive interpersonal structure. 'Second-personal desire' seeks something of or from a particular person who is the irreplaceable, intrinsic object of the desire by virtue of his or her significance to the desirer as a participant in an interpersonal relationship in which what is desired carries interpersonal significance. Such desires involve a wish that the other person will experience one's desire as a reason in a way that involves positive interpersonally directed emotional responsiveness to one's desire. Second-personal desire thus renders one vulnerable to distinctive forms of disappointment and to the possibility that the other person is neither positively motivated by, nor positively emotionally responsive to, the possibility of such disappointment. A distinctive form of positive emotional regard is thus always at issue in second-personal desire. This form of regard is not always owed, despite our craving for it—a fact that considerably complicates interpersonal interaction. The paper concludes with an argument that the participant reactive attitudes cannot be understood without the notion of second-personal desire and that second-personal desire is consequently crucial for an adequate understanding of the normative structure of interpersonal interaction.